On a conjecture of Andrews - Padmavathamma; T. G. Sudha (International Journal of Mathematics and Mathematical Sciences)
In this paper, we prove a particular case of a conjecture of Andrews on two partition functions Aλ,k,a(n) and Bλ,k,a(n).